2015
DOI: 10.1111/sms.12534
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of match‐running performance in elite male youth soccer players

Abstract: Although retained players covered more low-speed distance than released players, further study of the actions comprising low-speed distance during match-play is warranted to better understand factors differentiating retained and released players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 24 publications
12
60
0
1
Order By: Relevance
“…The emphasis on running-based performances for retention in both groups is likely related to the observation that match-running performance requirements (e.g. total and sprinting distance and peak game speed) typically increase in subsequent age groups following retention from U14 and U16 groups 56,62 . Furthermore, sprinting is an important action during decisive moments within football, such as reaching a ball before an opponent to score or prevent a goal 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis on running-based performances for retention in both groups is likely related to the observation that match-running performance requirements (e.g. total and sprinting distance and peak game speed) typically increase in subsequent age groups following retention from U14 and U16 groups 56,62 . Furthermore, sprinting is an important action during decisive moments within football, such as reaching a ball before an opponent to score or prevent a goal 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The mean age for the youngest group identified was 7.9 years [20], and the oldest group included 20-year-old players [57]. The majority of evaluations were from the European continent (62% of the total): England (14%) [13,15,19,26,33,44,47], Italy (10%) [20,24,37,57,66], Denmark [38,54,67], Portugal [43,62,65], Poland [23,55,64], Spain [56,61], San Marino [39,40], Norway [31,59], Turkey [29], Croatia [50] and Austria [49]. Other investigations were conducted in Asia, particularly in Qatar (18%) [12, 14, 17, 18, 41, 42, [35], Castellano et al [36], with permission Strict rules applied to Q2 (no information = 0 point; only age/age group was informed = 1 point; maturity offset also measured = 2 points); Q3 (0-1 item described = 0 point; 2-3 items described = 1 point; 4-5 items described = 2 points); and Q8 (description of mean, standard deviation and null hypothesis significance test [p-value] = 1 point; also included effect size/magnitude-based inferences = 2 points)…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The main study objectives identified were primarily to characterize general game demands (22%) [12,14,15,23,24,26,27,29,43,48,64] and to compare the running performance between playing positions (20%) [12,14,18,19,23,27,48,62,65,66], age groups (26%) [12-18, 20, 26, 27, 60, 66, 67] and match halves/periods (36%) [12, 14, 16, 20, 23, 24, 29, 31, 32, 37-40, 45, 48, 56, 57, 64]. Further studies also examined the influence of biological maturity [38,51,60], playing standards [33,38,48,54] and retained versus released players [15,19,26] and compared match running performances between game formats [37,54,61] and between specific training regimens [63]. Approximately one-third of all the studies evaluated relationships between the variables of match running performance and (1) anthropometric measures (e.g., height, body weight, and skinfolds) [50,60], (2) physiological markers [45,57] [71])…”
Section: Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the research that has examined youth and female populations there has been little justification provided for the speed zones selected, except that the thresholds were lowered to reflect the lower locomotor performance capacities of younger 44 and female cohorts. 45 One approach to has been to use mean cohort-specific physical fitness (ie, anaerobic threshold 46,47 ) or performance characteristics such as maximal sprint speed 48,49 from normative data sets to anchor player-independent (arbitrary) speed thresholds. The advantage of this approach is that the locomotor profile of the activity will be representative for the cohort, however, this will be limited by frequent changes in speed zones owing to squad composition and seasonal variations in physical fitness, precluding longitudinal analysis of locomotor trends.…”
Section: Speed Thresholdsmentioning
confidence: 99%